2016
DOI: 10.1016/j.mgene.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

African vs. Caucasian and Asian difference for the association of interleukin-10 promotor polymorphisms with type 2 diabetes mellitus (a meta-analysis study)

Abstract: BackgroundInterleukin-10 (IL-10) is a multifunctional regulatory cytokine that might be associated with increased risk of type 2 diabetes mellitus (T2DM). IL-10 gene polymorphisms have been reported to be associated with T2DM in several ethnic populations with controversial results.ObjectivesThis work is an updated meta-analysis aiming at the evaluation of the association between IL-10 gene polymorphisms: rs1800872 (− 592 C > A), rs1800896 (− 1082 A > G) and rs1800871 (− 819 C > T) with the risk of T2DM.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This polymorphism has been reported to be associated with type 2 diabetes [14], renovascular disease [15], and clinical outcomes in endstage renal disease [16]. We recently showed that the -1082A>G polymorphism is associated with diabetic retinopathy in type 2 diabetic patients (unpublished data).…”
Section: Introductionmentioning
confidence: 85%
“…This polymorphism has been reported to be associated with type 2 diabetes [14], renovascular disease [15], and clinical outcomes in endstage renal disease [16]. We recently showed that the -1082A>G polymorphism is associated with diabetic retinopathy in type 2 diabetic patients (unpublished data).…”
Section: Introductionmentioning
confidence: 85%
“…The -174 G allele of the IL-6 gene has been associated with the development of the metabolic syndrome and diabetes (Huth et al , 2006) as well as atherosclerosis (Chumaeva et al , 2014) in the context of chronic stress. The A allele of the -1082 polymorphism of the IL-10 gene has been associated with insulin resistance and obesity (Tarabay et al , 2016). MCP1 is considered to be a major attractant for macrophages in obesity, and the A allele of the G-2518 polymorphism is also associated with increased risk of diabetes and its complications (Zhang et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…According to studies, people with the AA genotype and the A allele have a higher susceptibility to juvenile idiopathic arthritis (JIA) [34], asthma [35], ischemic stroke [36] and Alzheimer [37] than people with the GG genotype. Conversely, in comparison with the AA and AG genotypes, the GG genotype of the IL-10 -1082 predisposes individuals to hepatitis B virus (HBV), hepatitis C virus (HCV) [38], acute pancreatitis [13] and type 2 diabetes [39]. In contrast in a study, type 2 diabetes was more common in people with homozygous AA and GG genotypes and the AG genotype was more prevalent in controls.…”
Section: Discussionmentioning
confidence: 99%